2022
DOI: 10.3389/fcimb.2022.838213
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of SARS-CoV-2 Infection-Induced Kidney Injury: A Literature Review

Abstract: The severe acute respiratory coronavirus 2 (SARS-CoV-2) has become a life-threatening pandemic. Clinical evidence suggests that kidney involvement is common and might lead to mild proteinuria and even advanced acute kidney injury (AKI). Moreover, AKI caused by coronavirus disease 2019 (COVID-19) has been reported in several countries and regions, resulting in high patient mortality. COVID-19‐induced kidney injury is affected by several factors including direct kidney injury mediated by the combination of virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 111 publications
0
29
0
3
Order By: Relevance
“…SARS-CoV-2 infection results in several extrapulmonary manifestations, including kidney and liver injury 30 . Angiotensin-converting enzyme 2 (ACE2), the entry receptor for SARS-CoV-2, is expressed in the liver and kidney 31 33 but viral replication in these organs remains controversial 34 , 35 . Both kidney and liver injury are likely multifactorial involving direct effects of the virus with inflammation and tissue damages, but also indirect effects resulting from systemic inflammation, dysregulated immune responses, endothelial dysfunction, and impaired organ crosstalk 32 , 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection results in several extrapulmonary manifestations, including kidney and liver injury 30 . Angiotensin-converting enzyme 2 (ACE2), the entry receptor for SARS-CoV-2, is expressed in the liver and kidney 31 33 but viral replication in these organs remains controversial 34 , 35 . Both kidney and liver injury are likely multifactorial involving direct effects of the virus with inflammation and tissue damages, but also indirect effects resulting from systemic inflammation, dysregulated immune responses, endothelial dysfunction, and impaired organ crosstalk 32 , 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme 2 (ACE2), the entry receptor for SARS-CoV-2, is expressed in the liver and kidney 31 33 but viral replication in these organs remains controversial 34 , 35 . Both kidney and liver injury are likely multifactorial involving direct effects of the virus with inflammation and tissue damages, but also indirect effects resulting from systemic inflammation, dysregulated immune responses, endothelial dysfunction, and impaired organ crosstalk 32 , 35 , 36 . Elevation of liver enzymes have been reported during SARS-CoV-2 infection, however, liver injury may be a reflection of a severe form of the disease 32 .…”
Section: Discussionmentioning
confidence: 99%
“…25 A hypothesis can be made through the mechanism of direct viral effect on the kidney and the indirect viral effect through the immunologic effect of cytokine storm combined with the dysregulation of the kidney in an SLE patient triggered the new onset of lupus nephritis or worsening. 26 The complications from out review show two cases with AKI 11 in our case , acute Respiratory Distress Syndrome 7,10 , bleeding symptoms et: gingival bleeding 6 , haemoptysis 9 , Intracranial Hemorrhage 8 , severe skin lesions 3, 12 , and altered mental status 3 with the outcome eight patients (80%) were survived and two patients including our case (20%) were passed away.…”
Section: Search Strategymentioning
confidence: 55%
“…Expression of ACE2 in vascular endothelial cells provides the pathophysiological basis for viral invasion. Histopathological examination of COVID-19 patients has revealed that SARS-CoV-2 directly invades endothelial cells, causing diffuse endothelial cell inflammation and microvascular damage, which most likely leads to the failure of multiple organs, including the kidneys ( 94 , 95 ). Hence, manipulation of DUSP6 holds great potential for the treatment of acute inflammatory diseases, such as AKI and COVID-19.…”
Section: Discussionmentioning
confidence: 99%